Development of solid lipid nanoparticle gel for transdermal delivery system of chaulmoogra oil - Rabea Parveen; Monalisha Samal; Nafis; Hayat M. Mukhtar; Sayeed Ahmad (Open Exploration Publishing Inc., 2023)
Aim: The main objective of the study was to formulate, evaluate and perform an optimization study of chaulmoogra oil-loaded solid lipid nanoparticles (SLNs) based gel. Methods: The study involves isolation, identification, and quantification of hydnocarpic acid (HA), using high-performance thin-layer chromatography (HPTLC) and characterization using ultraviolet (UV), nuclear magnetic resonance (NMR), and mass spectroscopy (MS), and differential scanning calorimetry (DSC). Different concentration of assorted solid lipids and surfactants was used for the preparation of SLN gel with the improved transdermal application. Size distribution, entrapping efficiency, transmission electron microscopy (TEM), and percent yield were tested for the prepared SLN and the characterization of SLN gel was evaluated on the basis of in vitro diffusion study, stability studies, homogeneity, and skin irritancy test. Results: The amount of HA quantified in the oil sample was found to be 54.84% w/w. The percent yield and entrapment efficiency (EE) of HA SLNs were 96.176 ± 1.338% and 90.2 ± 0.5% respectively. The in vitro percent cumulative drug release was 80.89% for the developed SLN, the homogeneity test showed no grittiness, and the prepared gel was found to be effective as it shows no signs of erythema post-treatment of 10 days. The in vitro dissolution studies showed better results for SLN gel when compared to SLN suspension. Conclusions: The nano-gel could be a better option for the topical delivery of herbal drugs with improved bioavailability providing several benefits over conventional formulation.